Absence of consistent sex differences in outcomes from symptomatic carotid endarterectomy and stenting randomized trials - Howard, Virginia J.; Algra, Ale; Howard, George; Bonati, Leo H.; de Borst, Gert J.; Bulbulia, Richard; Calvet, David; Eckstein, Hans-Henning; Fraedrich, Gustav; Greving, Jacoba P.; Halliday, Alison; Hendrikse, Jeroen; et al. (Stroke, 2021)
Download figureDownload PowerPoint
Gesehen am 28.05.2021